Ответы и объяснения

Лучший Ответ!
2013-09-21T21:36:10+00:00
2(x^2+9)=2(x+3)(x-3)           2x+6=2(x+3) 

9(x+5)   
    -    2x     = x+1            домножаем дробь на  2(x+3)(x-3) 
2(x+3)(x-3)       x-3       2(x+3)  

9(x+5)-2x(x+3)2=(x+1)(x-3)
9x+45-4x^2-12x=x^2-3x+x-3
9x+45-4x^2-12x -x^2+3x-x+3=0
48-x-5x^2=0
5x^2+x- 48=0
D=1-4(-48*5)=961=31^2
      -1+31                         -1-31
x1= 5*2      =3            x2=    5*2  =3.2
Ответ:x1=3 ; x2=3.2
2013-09-21T21:47:11+00:00
2(x^2+9)=2(x+3)(x-3)           2x+6=2(x+3) 

9(x+5)   
    -    2x     = x+1            домножаем дробь на  2(x+3)(x-3) 
2(x+3)(x-3)       x-3       2(x+3)  

9(x+5)-2x(x+3)2=(x+1)(x-3)
9x+45-4x^2-12x=x^2-3x+x-3
9x+45-4x^2-12x -x^2+3x-x+3=0
48-x-5x^2=0
5x^2+x- 48=0
D=1-4(-48*5)=961=31^2
      -1+31                         -1-31
x1= 5*2      =3            x2=    5*2  =3.2
Ответ:x1=3 ; x2=3.2

Как-то так.